KESESUAIAN MATERI PEYULUHAN TERHADAP KETERAMPILAN PETANI DALAM BERUSAHA TANI JAGUNG PADA DESA MADAMPI KECAMATAN LAWA KABUPATEN MUNA BARAT - Rosmina, Rosmina; Abdullah, Sukmawati; Isnian, Sitti Nur (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This study aims to determine thedetermine the suitability of agricultural extension materials to the skills of corn farmers in Madambi Village, Lawa District, West Muna Regency. This research was conducted using qualitative and quantitative methods, with 30 informants/respondents. Based on the results of the study, it can be concluded that the skills possessed by corn farmers in Madambi Village are still very strong with the teachings given by their ancestors where they still use them and still uphold the skills they have, the extension materials provided by an extension worker on corn farmers, showing that what was given by extension workers slowly began to be applied by corn farmers, although they still prioritize their own skills in farming corn, but over time farmers begin to understand and want to apply what has been taught by extension workers and the suitability of the material to skills corn farmers, are already in the moderate category where not all the problems experienced by farmers are in accordance with the material provided by the extension workers in Madampi Village, Lawa District, West Muna Regency.